From Procedural to Substantive Morality: Participation Problem on Lawmaking in Indonesia - Made Hendra Wijaya; Komang Sutrisni; Mohd Shafiee Bin Hamzah (Journal of Sustainable Development and Regulatory Issues (JSDERI), 2026)
This research demonstrates that lawmaking in Indonesia prioritizes procedural compliance while confining public participation to a symbolic and ineffective function in achieving substantive moral legitimacy. This orientation obstructs the transition from procedural morality to substantive morality and weakens the relationship between law and morality, which remains susceptible to political interests and lacks a coherent normative foundation. This research aims to examine the participation deficit in Indonesian lawmaking and to reconstruct the integration of morality by bridging the gap between formal participation and substantive moral legitimacy. This research employs a normative juridical method through conceptual, statutory, and comparative approaches to analyze the structure and function of participatory mechanisms. The findings reveal that symbolic participation constitutes the principal weakness in Indonesian lawmaking, as institutions satisfy procedural requirements without ensuring that public participation shapes normative outcomes, thereby producing a gap between formal legality and moral legitimacy. Comparative analysis demonstrates that effective institutional design enables participation to function as a substantive mechanism that articulates and realizes public interests within the legal system. This research develops a three-layer framework. First, the material element ensures that participation reflects substantive public interests and societal values within legal norms. Second, the formal element ensures that participatory procedures operate effectively, inclusively, and systematically within the lawmaking process. Third, the obligation element requires institutions to process, respond to, and incorporate public input into binding legal outcomes. This research concludes that reconstructing participation as a determinative institutional mechanism aligns legal processes with substantive moral outcomes, strengthens public trust, and secures sustainable legal legitimacy in Indonesia.